Seize the moment! Moments of suspended interaction as a patient resource for introducing psychosocial problems - Tarber, Christel (Academic Quarter | Akademisk kvarter, 2015)
Using the methodology of conversation analysis, this study focuses on patients’ disclosures of psychosocial problems during moments of suspended interaction, i.e. when the doctor is otherwise engaged. Contrary to most activities in the medical encounter, these disclosures are initiated by patients themselves. However, they are placed and designed so as not to require the doctor to respond, but rather to minimise the imposition on the doctor. Uptake, therefore, is not guaranteed. The placement of such disclosures exactly during suspended interaction displays a patient orientation to not derailing the progressivity of the consultation towards its end goal of treatment, an orientation also found by other interactional studies and shown to be related to low patient participation. The independent contribution of this study is that it enhances our understanding of the hitherto unexplored interactional barriers to the